Evaluation of black soldier fly larvae oil ( L.) calcium salt as an alternative fat source for laying quail diets - Hafidz Hukma Shabiyya Armaghoza; Setyo Nugroho; Sungkono Sungkono; Septiyanto Lukman Widodo; Bramasta Cahyo Saputra; Muhammad Anang Aprianto; Muhsin Al Anas (Animal Bioscience)
Objective This study aims to determine the effect of adding saponified black soldier fly larvae oil calcium salt (BSFLO-SCa) to quail feed as an alternative source of fat on laying performance, blood lipid profile, egg quality, and gene expression in lipid metabolism. Methods A total of 120 female Japanese quails (Coturnix japonica) aged 24 weeks were divided into 3 treatments, each with 8 replications, and each replication consisted of 5 quails in a completely randomized design. The applied treatments were the inclusion of basal feed as a control (T0) and basal feed supplemented with 1% BSFLO-SCa (T1) and 2% BSFLO-SCa (T2). Results The study indicated that the supplementation starting from 1% of BSFLO-SCa significantly decrease (p<0.05) in feed conversion ratio, blood lipid profile (total cholesterol, low density lipoprotein-cholesterol). Gene expression on fat synthesis of fatty acid synthase and cholesterol synthesis of 3-hydroxy-3-methylglutaryl coenzyme A reductase downregulated (p<0.05). In addition, the other parameters did not affect by supplementation of 1% BSFLO-SCa. The inclusion at 2% of BSFLO-SCa significantly increased (p<0.05) protein content of yolk and albumen, egg weight, egg shape index, and gene expression on fat oxidation of carnitine palmitoyltransferase-1. Egg yolk cholesterol, egg albumen ash, haugh unit, and gene expression on fat synthesis of acetyl-CoA carboxylase were significantly reduced (p<0.05). Conclusion Addition of 2% BSFLO-SCa in the feed improves performance, egg quality, and reduces cholesterol in the blood and eggs of quail. This improvement is accompanied by a reduction in the expression of key genes involved in lipid metabolism. BSFLO-SCa oil has the potential to be an alternative oil source in quail feed.